The role of deacetylase SIRT1 in allergic diseases - Lu, Yun; Tang, Xinyi; Wang, Wenxin; Yang, Jun; Wang, Shengjun (Frontiers in Immunology, 2024)
The silent information regulator sirtuin 1 (SIRT1) protein is an NAD + -dependent class-Ⅲ lysine deacetylase that serves as an important post-transcriptional modifier targeting lysine acetylation sites to mediate deacetylation modifications of histones and non-histone proteins. SIRT1 has been reported to be involved in several physiological or pathological processes such as aging, inflammation, immune responses, oxidative stress and allergic diseases. In this review, we summarized the regulatory roles of SIRT1 during allergic disorder progression. Furthermore, we highlight the therapeutic effects of targeting SIRT1 in allergic diseases.